PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN PAPAN ENERGI UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS IV SDN 3 BLIMBING KIDUL - Sa’adah, Amaliya Lailatus; Alviana, Kharisma Yogi; Ahsani, Eva Luthfi Fakhru (FASHLUNA, 2022)
This study aims to increase the activeness of students in science learning by using the Teams Games Tournament (TGT) cooperative learning model with the help of the media "Energy Change Board" in science learning class IV SDN 3 Blimbing Kidul. This study uses the Classroom Action Research (PTK) design by Kemmis and Mc.Taggart. This research model consists of the planning stage, the implementation stage and the observation and reflection stage. The research method used is descriptive qualitative. This study showed the results that: Student activity both in cycle I and cycle II showed a significant increase with the percentage in cycle I of 60% to 77% in cycle II. Based on these results, it can be concluded that student activity and learning outcomes have increased.